Effects of Doses Goat Manure and NPK Fertilizer on Growth and Yield of Pakcoy - Alvita, Alifah Manda; Fatmawaty, Andi Apriany; Muztahidin, Nur Iman; M., Kartina A. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The research aimed to know influence giving doses of goat manure fertilizer and NPK 16:16:16 fertilizer on the growth and result of plant pakcoy. This research completed in the experiment land Faculty of Agriculture, University of Sultan Ageng Tirtayasa at Sindangsari village, Pabuaran district Serang regency Banten Province and Laboratory of Soil and Agroclimate Faculty of Agriculture, University of Sultan Ageng Tirtayasa. The research used a factorial Randomized Group Design consist two factors. The first factor was a dose of goat manure fertilizer (P) consists of four levels; 141 g/polybag, 212 g/polybag, and 283 g/polybag, and 354 g/polybag. The second factor was a NPK 16:16:16 fertilizer; 1.1 g/polybag, 2.1 g/polybag, 3.2 g/polybag, and 4.2 g/polybag. The results of research showed the giving goat manure fertilizer a dose of 354 g/polybag gave influence a real of the plant height parameter, number of leaves, root length, and fresh weight of plant. The results of research showed the giving NPK 16:16:16 fertilizer a dose of 3.2 g/polybag gave influence a real of all observation parameters.